2021
DOI: 10.1136/bmjresp-2021-000899
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and neutrophil levels are potentially linked to progression to IPF for patients with indeterminate UIP CT pattern

Abstract: RationaleIdiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with poor prognosis. Identifying patients early may allow intervention which could limit progression. The ‘indeterminate for usual interstitial pneumonia’ (iUIP) CT pattern, defined in the 2018 IPF guidelines, could be a precursor to IPF but there is limited data on how patients with iUIP progress over time.ObjectiveTo evaluate the radiological progression of iUIP and explore factors linked to progression to IPF.MethodsWe perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…Fraser et al showed that monocyte levels were associated with the amount of fibrosis on CT scan,8 and large cohort studies from Scott linked blood monocyte levels to all-cause mortality,4 while Kreuter found an association with IPF progression (defined as ≥10% absolute decline in forced vital capacity (FVC%) predicted, ≥50 m decline in 6-min-walk distanc or death) within a year 9. In a smaller study, we found that neutrophil levels were highly significantly associated with progression of indeterminate UIP to diagnosis of IPF 10. These findings are supported by increasing understanding of the immune pathogenesis of IPF where innate immune cells like monocytes, monocyte-derived macrophages and neutrophils are likely to have a role in promoting fibroblast activity 11…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Fraser et al showed that monocyte levels were associated with the amount of fibrosis on CT scan,8 and large cohort studies from Scott linked blood monocyte levels to all-cause mortality,4 while Kreuter found an association with IPF progression (defined as ≥10% absolute decline in forced vital capacity (FVC%) predicted, ≥50 m decline in 6-min-walk distanc or death) within a year 9. In a smaller study, we found that neutrophil levels were highly significantly associated with progression of indeterminate UIP to diagnosis of IPF 10. These findings are supported by increasing understanding of the immune pathogenesis of IPF where innate immune cells like monocytes, monocyte-derived macrophages and neutrophils are likely to have a role in promoting fibroblast activity 11…”
Section: Introductionmentioning
confidence: 84%
“…First, we examined all the three main parameters of the blood leucocyte profile—neutrophils, lymphocytes and monocytes while Scott and Kreuter focused on monocyte levels only. We did this in part, because of our previous findings of correlation between neutrophils and progression of iUIP to definite/probable UIP on CT scans, 10 but also because there is ample evidence that neutrophils are involved in the immune-pathogenesis of IPF (described further below). 11 Although Scott also examined the transcriptome of blood immune cells, these were on RNA from stored peripheral blood mononuclear cells, where the neutrophil component would not have survived storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated in a cohort of patients with CT scans demonstrating iUIP that peripheral blood monocyte and neutrophil counts are implicated in progression to IPF [ 37 ], and the association of NLR, MLR and SIRI with mortality in IPF [ 38 ]. MLR has been used primarily to prognosticate in cancer studies in recognition that host systemic inflammatory responses influence tumour proliferation and disease progression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 facilitates the release of IL-6 and IL-8 from structural cells and augments neutrophilia ( 28 ). Monocyte and neutrophil levels were positively associated with progression from ‘indeterminate for usual interstitial pneumonia’ to IPF ( 29 ). A bronchoalveolar lavage (BAL) lower neutrophil-to-lymphocyte ratio has been demonstrated in sarcoidosis and chronic hypersensitivity pneumonitis compared to IPF patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%